On the performance of SCF in seismic isolation of the interior equipment of buildings. - Hamidi, M. (Earthquake engineering & structural dynamics.)
The dynamic response of equipment mounted on an isolated raised floor inside a building while the primary fixed base structure is subjected to harmonic and earthquake ground motions is numerically investigated. Sliding concave foundation (SCF) system is utilized for isolating the raised floor. The equations of motion for a MDOF shear building containing a SCF isolated raised floor with a mounted equipment are developed and the rigid link method is utilized to handle the non-linearity of the system. The equipment, which can be modelled as a SDOF or MDOF system, may represent a critical computer unit or telecommunication processing system. SCF can be used easily to achieve the desired long period, necessary for protecting sensitive equipment. In this investigation, the ability of SCF in reducing the acceleration level experienced by the equipment inside a building is demonstrated while the lateral displacement is still within an acceptable range. The analysis considered the case of equipment housed in the upper floors of a building where the acceleration is amplified and the motion contains strong components at long periods. For this purpose, different excitations including both harmonic and real earthquake ground motions are employed and the performance of the system is evaluated.